KINETICS OF PETROLEUM GENERATION BY PROGRAMMED-TEMPERATURE CLOSED-VERSUS OPEN-SYSTEM PYROLYSIS - Schenk H.J.; Horsfield B. (My University, 1993)
Bulk petroleum generation by programmed-temperature pyrolysis of immature (Rr = 0.48%) Posidonia (Toarcian) Shale samples at heating rates of 0.1, 0.7, and 5.0 K/min has been studied comparatively under open- and closed-system conditions, using the microscale sealed vessel (MSSV) technique in the latter case. The comparison of formation rates required a differentiation (vs. temperature) of closed-system cumulative product evolution profiles. The kinetic analysis assuming twenty-five first order parallel reactions with activation energies regularly spaced between 46 and 70 kcal/mol and a single preexponential factory yielded the same value of A = 1.08 · 1016 min−1 and very similar petroleum potential vs. activation energy distributions centered around 54 kcal/mol in both cases. In particular, both approaches turned out to be in excellent agreement with respect to predicting temperature ranges of oil and gas formation under geological heating conditions. This is in contrast to the case of petroleum yield assessment which appears to be more system-dependent.